2010
DOI: 10.1007/s00253-010-2810-1
|View full text |Cite
|
Sign up to set email alerts
|

Serratia odorifera: analysis of volatile emission and biological impact of volatile compounds on Arabidopsis thaliana

Abstract: Bacteria emit a wealth of volatiles. The combination of coupled gas chromatography/mass spectrometry (GC/MS) and proton-transfer-reaction mass spectrometry (PTR-MS) analyses provided a most comprehensive profile of volatiles of the rhizobacterium Serratia odorifera 4Rx13. An array of compounds, highly dominated by sodorifen (approximately 50%), a bicyclic oligomethyl octadiene, could be detected. Other volatiles included components of the biogeochemical sulfur cycle such as dimethyl disulfide (DMDS), dimethyl … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
162
1
2

Year Published

2012
2012
2013
2013

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 136 publications
(173 citation statements)
references
References 57 publications
5
162
1
2
Order By: Relevance
“…Our observations that DMDS promotes plant growth differ in part from those of Kai et al (2010) in that fumigation of Arabidopsis seedlings with DMDS suppressed growth irrespective of the concentration applied. In our experimental setup (MM2 medium supplemented with different amounts of SO 4 22 ), we found positive effects of 500 µg DMDS per Petri dish on the growth of Arabidopsis, as we did with N. attenuata seedlings (see Supplemental Figure 10 online).…”
Section: Discussioncontrasting
confidence: 50%
See 2 more Smart Citations
“…Our observations that DMDS promotes plant growth differ in part from those of Kai et al (2010) in that fumigation of Arabidopsis seedlings with DMDS suppressed growth irrespective of the concentration applied. In our experimental setup (MM2 medium supplemented with different amounts of SO 4 22 ), we found positive effects of 500 µg DMDS per Petri dish on the growth of Arabidopsis, as we did with N. attenuata seedlings (see Supplemental Figure 10 online).…”
Section: Discussioncontrasting
confidence: 50%
“…We cannot exclude the possibility that other S-containing VOCs, not detected by methods we used (SPME coupled to GC-MS), might also have been transferred through the headspace and assimilated. For example, other sulfurous VOCs, such as methanethiol, dimethyl sulfide, and dimethyl trisulfide, are commonly produced by a range of microbes (Farag et al, 2006;Kai et al, 2010;Minerdi et al, 2011). Furthermore, S-methyl pentanethioate (see Supplemental Table 2 online), which is emitted in trace amounts, might have contributed to the radioactive signal.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the plant roots, there are other natural sources that may contribute to sulfide emissions. Several soil-dwelling microorganisms are known to produce volatile sulfides, including DMDS ( [126], [127]). The low levels of sulfides emerging from control plants show that the direct contribution -if anyof soil dwelling microorganisms to these emissions is small (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Head space analysis would in principle allow bacterial cultures to be characterized on line without manual manipulation. It has been shown that it is possible to measure Volatile Organic Compounds (VOCs) from the headspace of bacterial cultures using Proton Transfer Reaction Mass Spectrometry (PTR-MS) ( [131]; [40]; [127]) or related methods [132]. Those systems have provided consistent evidence that various microbes and mycobacteria produce distinctive patterns of VOCs.…”
Section: Introductionmentioning
confidence: 99%